A new improved catalyst for the palladium-catalyzed amination of aryl chlorides - Ehrentraut, Andreas; Zapf, Alexander; Beller, Matthias (Journal of molecular catalysis. A, Chemical, 2002)
The catalytic amination of aryl chlorides is an interesting subject for the fine chemical industry due to the importance of anilines as building blocks for pharmaceuticals, agrochemicals and new materials. Here we report the application of our recently developed di(1-adamantyl)alkylphosphines for the palladium-catalyzed amination of non-activated aryl chlorides. In general, excellent yields of amination products are obtained using 0.5 mol% of palladium(II)acetate and 1 mol% of di(1-adamantyl)- n-butylphosphine ( 12) in toluene at 120 °C. Remarkable results are obtained for the coupling of hindered amines with sterically congested aryl chlorides. Comparing the new catalyst system with previously reported best palladium catalysts we found in all cases improved yields of amination products in the presence of our ligands.